PERAN MOTIVASI KERJA PADA ORGANISASI DI INDONESIA - Muthia Sandra Riphasa; Marnita Marnita; Mahdum Mahdum; Dahnilsyah Dahnilsyah; Fadly Azhar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to provide a comprehensive mapping of the role of work motivation in Indonesian organizations through a Systematic Literature Review (SLR) of 15 national and international articles published between 2020 and 2025. The review is motivated by inconsistent empirical findings regarding the relationship between work motivation and employee performance, indicating that the effectiveness of motivation is strongly shaped by contextual factors such as organizational culture, leadership style, compensation, and work structure. The SLR method involved systematic database searches, article selection based on inclusion criteria, full-text reading, data extraction, and thematic synthesis to identify patterns of relationships among variables. The analysis reveals three main patterns: motivation as a direct determinant of performance, motivation functioning as a mediating variable between organizational factors and performance, and motivation that shows no significant effect, particularly within bureaucratic government institutions. These findings demonstrate that work motivation is not universal but is highly dependent on the organizational ecosystem. The novelty of this study lies in its thematic mapping of the most recent five-year literature, integrating various organizational contexts in Indonesia to provide an updated and comprehensive scientific overview that supports the development of evidence-based human resource management policies